Crystals 2017 Best Paper Award - Crystals Editorial Office (Crystals, 2017)
Crystals is instituting the Best Paper Award to recognize the outstanding papers published in the journal. We are pleased to announce the “Crystals Best Paper Award” for 2017. [...]